Two-part fractional regression model for the demand for risky assets - Yerokhin, O; Stavrunova, O (My University, 2012)
Empirical studies of household portfolio choices are often interested in quantifying the effects of various covariates on the fraction of a household's wealth invested in risky assets such as common stocks. The preferred econometric specification in these studies is the two-limit Tobit model, which can accommodate the fractional nature of the dependent variable. However, it is restrictive, because it assumes that the same data generating process determines both whether households participate in the stock market and the fraction of wealth invested in stocks. This article demonstrates that, in this setting, a two-part version of the fractional response model of Papke and Wooldridge (1996) constitutes an attractive alternative to Tobit by comparing the performance of the two models using data on portfolio choices of Australian households. We find that (1) the Tobit model is rejected by our data in favour of a two-part specification; and (2) marginal effects of covariates on the share of risky assets conditional on participation estimated from Tobit are confounded by the effects of these covariates on the participation decision.
Keywords: Income & Finance -- Wealth; Income & Finance -- Assets; Income, wealth and finances; Income & Finance; Wealth; Assets; Income, wealth and finances